Answer:
![g(x)=\sqrt[3]{x-3}+4](https://tex.z-dn.net/?f=g%28x%29%3D%5Csqrt%5B3%5D%7Bx-3%7D%2B4)
Step-by-step explanation:
The function g(x) is a shifted version of the function f(x); f(x) is shifted by 3 along x-axis and by 4 along y-axis.
Another way of thinking about this is that the function g(x) contains points (3, 4); therefore,
which goes through the point (3, 4).
Answer:
D. -2s
Step-by-step explanation:
s+s-4s
=1s+1s-4s
=(1+1-4)s
=-2s
What is the product? I cannot help you if I don't know the product..